'It׳s quite simple, really': Shifting forms of expertise in TV documentaries. (September 2016) - Chovanec, Jan
Abstract: In this paper, I analyse how expertise is discursively negotiated in TV documentary programmes. While previous research has explored the relationship between the 'lay' and the 'expert' dimensions in various public participation programmes, this paper focuses on a TV programme format that is based on the cooperative interaction between professionals who differ in the extent of their knowledge and experience. The paper notes that while expertise is unevenly distributed between the voiceover, the presenter and the expert, these parties complement each other in explaining complex phenomena for the benefit of the audience. Using data from the documentary series How Britain Worked, I argue that as long as the presenter possesses some technical expertise, he may be positioned as a semi-expert between the true expert and the lay audience, even when he simultaneously acts in other contexts as a novice acquiring the specialized expertise needed for his quest. Thus, rather than demonstrating his own knowledge and skills, the presenter mediates expertise for the benefit of the audience. The mediating role is attested by the presenter׳s frequent shifts of footing in and out of the conversational interaction with the true expert, who may end up assuming a background role of expert support. Highlights: In TV documentaries, expertise is unevenly distributed between the voiceover, experts, the presenter and the audience. The voiceover provides authoritative information in a separate communicative level. The presenter acts as a semi-expert between real experts and the lay audience. The presenter's level of expertise changes dynamically in various scenes. Expertise is discursive managed through presentation, negotiation, mediation and acquisition.